THE EFFECTIVENESS OF USING ELECTRONIC DICTIONARY TO TEACH VOCABULARY VIEWED FROM STUDENTS’ SELF-EFFICACY - Rohmatillah, Rohmatillah (Universitas Islam Negeri Raden Intan Lampung, 2013)
The objectives of the research are to find out whether: (1) Electronic Dictionary ismore effective than Printed Dictionary in teaching Vocabulary; (2) the studentswith high level of self-efficacy have better vocabulary mastery than those withlow level of self-efficacy; and (3) there is an interaction between teachingmedia and students’ self-efficacy. The experimental research was carried out atInstitut Agama Islam Negeri Raden Intan, Lampung in the Academic Year of2012/2013, from October to December 2012. The samples which took two classeswere done using cluster random sampling technique. Each class was divided intotwo groups students who have high and low self-efficacy. The techniques whichwere used to collect the data were questionnaire and vocabulary test. The twoinstruments were tried out to obtain valid and reliable items. The researcheranalyzed the data using ANOVA or analysis of variance and Tukey test. Theresult of research findings leads to the conclusion that: (1) using electronicdictionary is more effective than printed dictionary to teach vocabulary for thefirst semester students of English Education of Institut Agama Islam NegeriRaden Intan, Lampung; (2) students having high self-efficacy have bettervocabulary mastery than students having low self-efficacy; and (3) there is aninteraction between teaching media and self-efficacy. Results indicated that anElectronic Dictionary is an effective learning tool that can enhance vocabularylearning.